The Association of Family Support and Health Education with the Status of Overweight and Obesity in Patients with Type 2 Diabetes Receiving Outpatient Treatment: Evidence from a Hospital in Vietnam - Nguyen Thanh Ha; Duong Truong Sinh; Le Thi Thu Ha (SAGE Publishing, 2021)
This study aims to establish the association of family support and nutrition and health education by health workers with the status of overweight and obesity among patients with type 2 diabetes mellitus (T2DM) receiving outpatient treatment at a hospital. This descriptive cross-sectional study was conducted on 280 outpatients with type 2 diabetes at Bach Mai hospital from December 2019 to September 2020 by using assessments of anthropometric parameters and examining dietary habits and family support, as well as nutrition and health education and counseling by health workers. The prevalence of overweight and obesity in patients with T2DM was 35.4% (51.2% in men and 22.2% in women; P  < .05). Patients never or rarely supported by their families or counseled by health workers were more vulnerable to overweight and obesity than those who frequently received support and counseling (OR = 1.41 vs 2.06; P  < .05). Family support and counseling from health workers play a crucial role in promoting and sustaining healthy dietary habits and proper physical exercise in diabetic patients, contributing to their lowered risk of overweight and obesity.